NOISE CHARACTERISTICS OF BALL BEARING LUBRICATED WITH ENGINE OIL ENHANCED WITH HEXAGONAL BORON NITRIDE PARTICLE ADDITIVE - Al-Ghaili, K.; Ismail, R.; Apandi, N.S.R.; Azmi, M.S.; Cartmell, M.P. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The use of rolling element bearings is significant in most mechanical applications. Thus, the reliability and efficiency of the mechanical machines depend critically on the health of the rolling bearings. Vibration and noise generated by bearings are one of the big concerns in the industry since it limits the performance of the machines. The aim of this paper is to determine the noise characteristics for ball bearings lubricated with hexagonal Boron Nitride (hBN) nanoparticles additives in engine oil with different volume concentrations of hBN namely 0.1%, 0.2%, 0.3%, 0.4%, 0.5%. A test rig consisted of a motor that drives the system, coupling, rotor to support the imposed loads and a ball bearing in which its performance to be validated. Samples of hBN nano-lubricant with different % volume of hBN concentrations were prepared using the ultrasonic homogenizing technique. Three conditions of ball bearing investigated which were healthy bearing, inner defected bearing and outer defected bearing. Sound Level Meter was used to record the noise level for 10 minutes for each concentration and load condition and the average of the equivalent sound level for that period was calculated. The measurement of noise level has shown that the imposed load and concentration of hBN nanoparticles in the lubricant have a significant contribution to the noise level of the bearing. The noise level increased slightly with the increase of unbalance imposed load while the noise level decreased with the addition of the 0.2% volume concentration of hBN nanoparticles. The overall performance has shown a reduction in noise level.